Friction-Induced Pain: From Skin Surface to Brain Activation - Xingxing Fang; Wei Tang; Shousheng Zhang; Yanze Wu; Yifeng Zeng; Yangyang Xia; Ming Zhang (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
The interface friction between prosthetic socket and residual limb tends to cause skin injury and pain. The frictional pain was systematically studied based on skin tribological behaviors and brain activation. The results showed that the skin frictional pain was affected by the combination of friction and mechanical properties of anatomic regions and liner materials. The low elastic modulus and good viscoelasticity of anatomic regions or high adhesion and good compliance of liner materials both can increase the frictional pain threshold and decease the injury. The main brain activation related to frictional pain located in the primary somatosensory cortex (SI), secondary somatosensory cortex (SII), and prefrontal cortex (PFC). The brain negative activation increased and the activation area decreased with the increased pain intensity. The features of $α $ activity, $β $ activity, and $α _{\text {peak}}$ extracted from EEG signals were effective in the recognition of pain state, but cannot recognize the pain intensities.